The Role of the Unity of Knowledge and Example in the Improvement of Personal Moral Qualities - Amonlaev Abdurasul Khakimovich (Genius Journals, 2022)
This article describes the role of the unity of knowledge and example in the improvement of moral qualities of a person. Also, in the matter of knowledge and wisdom, the importance of the teachings of the enlightened people to the spiritual maturity of a person is analyzed.
Keywords: Knowledge; example; personality; morality